A conceptual paper on the best financial management model that has become the practice of the Malay in Klang Valley / Leylawati Joremi - Joremi, Leylawati (Universiti Teknologi MARA, Shah Alam, 2019)
This conceptual paper is presented with the intention to study the best practice model of financial management, which has become the practice of the Malay in Klang Valley. It begins by reviewing the literature on household financial management and the behavior of households against finances and debt. The theory of utility and the life-cycle hypothesis were used as the basis of the study. This study is inspired by the concerns of the government and the public on the growing bankruptcy issue in Malaysia. Many previous quantitative studies discussed the flaws in money management. This study, however, slightly different. Using a qualitative method, it intends to look at the best practices implemented by the household in managing family finances. The findings can add value to today's body of knowledge. Identified themes can be used to design financial modules which are more compatible to be used by all levels of society.